X-ray observations of luminous dusty quasars at z > 2. Issue 3 (5th May 2020) - Lansbury, G B; Banerji, M; Fabian, A C; Temple, M J
ABSTRACT: We present new X-ray observations of luminous heavily dust-reddened quasars (HRQs) selected from infrared (IR) sky surveys. HRQs appear to be a dominant population at high redshifts and the highest luminosities, and may be associated with a transitional 'blowout' phase of black hole and galaxy co-evolution models. Despite this, their high-energy properties have been poorly known. We use the overall sample of 10 objects with XMM–Newton coverage to study the high-energy properties of HRQs at $\langle$ L bol $\rangle$ =10 47.5 erg s −1 and $\langle$ z $\rangle$ =2.5. For seven sources with strong X-ray detections, we perform spectral analyses. These find a median X-ray luminosity of $\left\langle L_{\rm 2\!-\!10\, keV} \right\rangle = 10^{45.1}$ erg s −1, comparable to the most powerful X-ray quasars known. The gas column densities are N H = (1–8) × 10 22 cm −2, in agreement with the amount of dust extinction observed. The dust-to-gas ratios are sub-Galactic, but are higher than found in local AGN. The intrinsic X-ray luminosities of HRQs are weak compared to the mid-IR ($L_{\rm 6\, μ m}$ ) and bolometric luminosities ( L bol ), in agreement with findings for other luminous quasar samples. For instance, the X-ray to bolometric corrections range from κ bol ≈ 50 to 3000. The moderate absorption levels and accretion rates close to the Eddington limit ($\langle$ λ Edd $\rangle$ =1.06) are in agreement with a quasar blowout phase. Indeed, we find that the HRQs lie in the forbidden region of the N H – λ Edd plane, and therefore that radiation pressure feedback on the dusty interstellar medium may be driving a phase of blowout that has been ongoing for a few 10 5 yr. The wider properties, including [O iii ] narrow-line region kinematics, broadly agree with this interpretation.